2010
DOI: 10.3892/etm.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Serum harvested from heifers one month post-zeranol implantation stimulates MCF-7 breast cancer cell growth

Abstract: Abstract. Breast cancer is a serious disease in the uS. numerous risk factors have been linked to this disease. the safety of using growth promoters, such as zeranol, remains under debate due to the lack of sufficient in vitro and in vivo evidence. using celltiter 96™ aqueous non-radioactive cell proliferation assay, real-time pcr and Western blot analysis, we evaluated the effects of sera harvested from experimental and control heifers before and after one month of zeranol implantation on the growth of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Follow-up work demonstrated that ZER is comparable to natural estrogen (estradiol) and the synthetic estrogen diethylstilbestrol (DES) in its ability to transform MCF-10A human breast epithelial cells to a pre-cancerous profile in vitro [ 639 ]. Preliminary data indicate that serum from ZER-treated beef cattle can stimulate the proliferation of normal breast epithelial cells and the transformation of breast tumor cells in vitro [ 640 , 641 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%
“…Follow-up work demonstrated that ZER is comparable to natural estrogen (estradiol) and the synthetic estrogen diethylstilbestrol (DES) in its ability to transform MCF-10A human breast epithelial cells to a pre-cancerous profile in vitro [ 639 ]. Preliminary data indicate that serum from ZER-treated beef cattle can stimulate the proliferation of normal breast epithelial cells and the transformation of breast tumor cells in vitro [ 640 , 641 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%
“…BC in women ranks among the most common malignant tumors; it is also second chief reason of mortality in industrialized countries (Arshi et al 2018). In 2008, the American Cancer Society estimated that in 2014, roughly 182,500 women would be diagnosed with Taherzadeh-Soureshjani and Chehelgerdi Cancer Nano (2020) 11:11 BC and 40,500 women would die because of BC (Ye et al 2010). In Iran, the average age of diagnosis of BC is roughly 15 years lower than the reported cases in western countries (Mousavi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory’s recent experimental results showed that pre-adipocytes isolated from the cattle 60 days post Z-implantation (72 mg/pellets/animal) grow about 12-times faster than the pre-adipocytes isolated from control cattle [ 11 ]. Treatment with 0.2, 1 and 5% Z sera (ZS) harvested from the cattle 30 days post implantation in culture medium significantly stimulated MCF-10A and MCF-7 cell growth [ 12 , 13 ]. We also have evidence showing that leptin, which plays a role in breast cancer development in obesity, induces human breast cancer epithelial cell sensitivity to Z [ 14 ].…”
Section: Introductionmentioning
confidence: 99%